Diagnostic Accuracy of Lung Ultrasound in Patients with Community-Acquired Pneumonia: A Single Center Observational Study - Elsayed, Marwa; Hesham, Moataz Ahmed; Kamel, Khaled Mahmoud; Nassar, Yasser Sadek (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Pneumonia is a prevailing and severe infectious disease that can lead to increased fatality. AIM: We conducted this study to assess the role of lung ultrasound (LUS) in the diagnosis of community-acquired pneumonia (CAP) in comparison to CXR and CT Chest. METHODS: An observational study on 120 patients with suspected CAP was done in the ICU of the Critical care department at Cairo University Hospital. Clinical and laboratory data were recorded on admission including different scoring systems (SOFA, APACHE II, confusion, uremia, respiratory rate and blood pressure 65, and pulmonary severity index). All patients, within 6 h of admission, were investigated by a LUS, CXR, and CT Chest. All imaging techniques were repeated after 48 h if the initial CT chest was negative. RESULTS: The study population had a mean age of 70.6 ± 6.9-years-old, most of them were male (75.8%). Using CT chest as a reference imaging tool to confirm the diagnosis of pneumonia, LUS showed 94.1% sensitivity, 97.1% specificity, positive predictive value (PPV) 98.8%, negative predictive value (NPV) 87.2%, accuracy 95.0%, and area under a curve (AUC) 0.92. LUS was found to be a highly significant imaging tool in predicting diagnosis of pneumonia (p < 0.001). Chest X-ray had 69.4% sensitivity, 94.3% specificity, PPV 96.7%, NPV 55.9%, 76.6% accuracy, and AUC 0.6 in the detection of pneumonia. CXR was found to be an insignificant Imaging tool in predicting diagnosis of pneumonia (P = 0.19). CONCLUSION: LUS is a very promising, sensitive, and feasible imaging tool in the diagnosis of CAP in comparison with CT chest.